NMDA receptor activation and respiratory chain complex V inhibition contribute to neurodegeneration in d-2-hydroxyglutaric aciduria - Kölker, Stefan; Pawlak, Verena; Ahlemeyer, Barbara; Okun, Jürgen G.; Hörster, Friederike; Mayatepek, Ertan; Krieglstein, Josef; Hoffmann, Georg F.; Köhr, Georg (European journal of neuroscience, 2002)
The inherited neurometabolic disease d-2-hydroxyglutaric aciduria is complicated by progressive neurodegeneration of vulnerable brain regions during infancy and early childhood, frequently presenting with hypotonia, epilepsy and psychomotor retardation. Here, we report that the pathogenetic role of the endogenously accumulating metabolite d-2-hydroxyglutarate (D-2), which is structurally similar to the excitatory amino acid glutamate, is mediated by at least three mechanisms. (i) D-2-induced excitotoxic cell damage in primary neuronal cultures from chick and rat involved N-methyl-d-aspartate (NMDA) receptor activation. Indeed, D-2 activated recombinant NMDA receptors (NR1/NR2A, NR1/NR2B) but not recombinant alpha-amino-3-hydroxy-5-methyl-4-isoxazole (AMPA) receptors in HEK293 cells. (ii) Fluorescence microscopy using fura-2 as a calcium indicator and the oxidant-sensitive dye dihydrorhodamine-123 revealed that D-2 disturbed intracellular calcium homeostasis and elicited the generation of reactive oxygen species. (iii) D-2 reduced complex V (ATP synthase) activity of the mitochondrial respiratory chain, reflecting an impaired energy metabolism due to inhibition of ATP synthesis but without affecting the electron-transferring complexes I-IV. Thus, D-2 stimulates neurodegeneration by mechanisms well-known for glutamate, NMDA or mitochondrial toxins. In conclusion, excitotoxicity contributes to the neuropathology of d-2-hydroxyglutaric aciduria, highlighting new neuroprotective strategies.